Nuclear behaviour in Coprinus disseminatus and Panaeolus papilionaceus - S.P. LAL, MANISHA SHANKAR* and (Indian Phytopathology, 2002)
The Nuclear behaviour in the basidia of Coprinus disseminatus and Panaeolus papilionaceus is being reported.